High spatial‐resolution monitoring to investigate nitrate export and its drivers in a mesoscale river catchment along an anthropogenic land‐cover gradient. Issue 12 (14th December 2021) - Bujak, Izabela; Müller, Christin; Merz, Ralf; Knöller, Kay
Abstract: Nitrate monitoring is commonly conducted with low‐spatial resolution, only at the outlet or at a small number of selected locations. As a result, the information about spatial variations in nitrate export and its drivers is scarce. In this study, we present results of high‐spatial resolution monitoring conducted between 2012 and 2017 in 65 sub‐catchments in an Alpine mesoscale river catchment characterized by a land‐use gradient. We combined stable isotope techniques with Bayesian mixing models and geostatistical methods to investigate nitrate export and its main drivers, namely, microbial N turnover processes, land use and hydrological conditions. In the investigated sub‐catchments, mean values of NO3 − concentrations and its isotope signatures (δ 15 NNO3 and δ 18 ONO3 ) varied from 2.6 to 26.7 mg L −1, from −1.3‰ to 13.1‰, and from −0.4‰ to 10.1‰, respectively. In this study, land use was an important driver for nitrate export. Very strong and strong positive correlations were found between percentages of agricultural land cover and δ 15 NNO3, and NO3 − concentration, respectively. Mean proportional contributions of NO3 − sources varied spatially and seasonally, and followed land‐use patterns. The mean contribution of manure and sewage was much higher in the catchments characterized by a high percentage of agricultural and urban land cover comparing to forested sub‐catchments. Specific NO3 − loads were strongly correlated with specific discharge and moderately correlated with NO3 − concentrations. The nitrate isotope and concentration analysis results suggest that nitrate from external sources is stored and accumulated in soil storage pools. Nitrification of reduced nitrogen species in those pools plays the most important role for the N‐dynamics in the Erlauf river catchment. Consequently, nitrification of reduced N sources was the main nitrate source except for a number of sub‐catchments dominated by agricultural land use. In the Erlauf catchment, denitrification plays only a minor role in controlling NO3 − export on a regional scale. Abstract : We integrated results of the BMM with informative priors and top‐kriging. Reduced N stored in soil is an important source for stream N in a mesoscale catchment. Manure and sewage is the main NO3 − source in agricultural sub‐catchments. Denitrification played only a minor role in controlling regional scale NO3 − export.